Channel estimation and performance analysis for uplink SCMA system - Xian’an HU; Xiangnian ZENG (Dianxin kexue)
There are two types of physical mapping for SCMA named RE-Sparse SCMA and RB-Sparse SCMA.A frequency division multiplexing (FDM) based pilot pattern was proposed for RE-Sparse SCMA,and existing code division multiplexing pilot patterns based on cyclic shift and orthogonal cover code (OCC) were considered.Under different frequency selective channels,simulation and evaluation work for the two mapping schemes of SCMA had done.Besides,a target user selection strategy was proposed for existing SIC-MPA.Analytical simulation results show that both OCC and FDM can improve system performance with slot fading channel.Compared with RE-Sparse SCMA,RB-Sparse SCMA with partially frequency orthogonal pilot pattern enjoys better performance gain,and it is more applicable for realistic multi-user SCMA scenario.